2003
DOI: 10.1002/mds.10463
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation in Parkinson's disease: PET changes correlate with the amount of grafted tissue

Abstract: We compared the striatal uptake of [(18)F]fluorodopa with [(76)Br]-FE-CBT, a positron emission tomography (PET) ligand of the dopamine transporter (DAT), which estimates the density of dopamine nerve terminals, in 6 patients with Parkinson's disease grafted with fetal mesencephalic cells. There was no change in DAT ligand binding in the grafted putamen, despite a significant increase of [(18)F]fluorodopa uptake. This finding suggests that the clinical benefit induced by the graft is more related to increased d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 24 publications
(39 reference statements)
1
38
0
Order By: Relevance
“…Clinical trials using transplants of human embryonic mesencephalic tissue in PD patients have revealed that grafted DA neurons can survive, appropriately differentiate and reinnervate the striatum, release DA, and become functionally integrated into the host neural circuitries (Lindvall et al, 1990;Kordower et al, 1995;Piccini et al, 1999;Mendez et al, 2005). However, the magnitude of transplant-induced functional outcome has been variable with some patients displaying major improvements and others no or only minor clinical response (Peschanski et al, 1994;Hagell et al, 1999;Hauser et al, 1999;Brundin et al, 2000;Mendez et al, 2000;Freed et al, 2001;Cochen et al, 2003;Olanow et al, 2003) [for detailed review of the literature, see Winkler et al (2005)]. Importantly, the extent of DA neurodegeneration and the preoperative distribution and magnitude of loss of DA innervation in the forebrain have not been so far taken into consideration, neither in the selection of patients for grafting nor in the design of the transplant procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials using transplants of human embryonic mesencephalic tissue in PD patients have revealed that grafted DA neurons can survive, appropriately differentiate and reinnervate the striatum, release DA, and become functionally integrated into the host neural circuitries (Lindvall et al, 1990;Kordower et al, 1995;Piccini et al, 1999;Mendez et al, 2005). However, the magnitude of transplant-induced functional outcome has been variable with some patients displaying major improvements and others no or only minor clinical response (Peschanski et al, 1994;Hagell et al, 1999;Hauser et al, 1999;Brundin et al, 2000;Mendez et al, 2000;Freed et al, 2001;Cochen et al, 2003;Olanow et al, 2003) [for detailed review of the literature, see Winkler et al (2005)]. Importantly, the extent of DA neurodegeneration and the preoperative distribution and magnitude of loss of DA innervation in the forebrain have not been so far taken into consideration, neither in the selection of patients for grafting nor in the design of the transplant procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic Grafts Can Survive and Become Morphologically Integrated in the PD Patient's Brain Following implantation of postmitotic DA neuroblasts from the ventral mesencephalon of 6-to 9-weekold human fetuses, positron emission tomography (PET) detected increases in 6-L-[ 18 F]-fluorodopa ( 18 F-dopa) uptake ( Fig. 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and histopathological studies have shown long-term, extensive synaptic reinnervation in the striatum [13,[20][21][22][23][24][25][26][27].…”
Section: Can Da Neurons Be Replaced and Neural Grafts Have Functionalmentioning
confidence: 99%
“…Importantly, the recovery of dopamine function being was found to be dependant on the amount of fetal tissue implanted [107]. Recently, the graft's functionality has been investigated by Piccini and colleagues, where DA release from the fetal DA neurons was visualized using 11 C-labeled Raclopride [89].…”
Section: Applications Of Pet In Neurodegenerative Statesmentioning
confidence: 99%